Peran Electronic Word Of Mouth (Ewom) Di Dalam Perbelanjaan Skincare Generasi Z (Studi Deskriptif Kualitatif Pada Pengguna Twitter) - Aziza, Fairuzia (2021)
Generation Z is very involved in eWOM on social media, especially in their shopping journey. However, in determining actions that refer to purchasing decisions, they need accurate information and will mix information from one source with another. 80% of those who plan to make a purchase online will look for consumer reviews on the internet and social media (eWOM) before making a purchase decision. In 2012, the well-known advertising agency Leo Burnett described Social Shoppers, referring to a group of people who involve social media in their shopping journey. Interestingly, Generation Z dominates the demographic of the Social Shopper. They are considered smart in filtering information, so conventional advertising is not very effective at targeting them. Instead, they rely on the opinions of others to help them make purchasing decisions. The method used is a descriptive qualitative method for 5 skincare users who use Twitter social media. The data analysis technique used in this research is the Analysis Interactive Model which consists of data reduction, data presentation, and conclusion drawing and verification. The data validity technique used in this research is a triangulation of data sources. The results of this study indicate that cognition continues to develop because of the online forum for mutual influence combined with Twitter's social media design that makes it easier for Generation Z to find and engage in information about skincare products. Information about skincare products is obtained intentionally or unintentionally, and its role in generation Z skincare shopping is as social validation, reducing risk from product use, reducing time and effort, benefiting from social interaction, and getting an education on product usage information.